Suitabilityof Different Winter Vegetables with Sweet Gourd - Kakon, SS; Chowdhury, JA; Bazzaz, MM; Alam, MM; Begum, AA; Aziz, MA (Bangladesh Agronomy Journal, 2019)
The experiment was conducted at Joydebpur and Rajbari Farm of Bangladesh Agricultural Research Institute during two successive rabi seasons (2014-16) to find out the suitable vegetable for intercropping with sweet gourd for higher productivity and economic return. Six intercrop combinations of sweet gourd and vegetables viz., T1 = Sole sweet gourd, T2 = Sweet gourd (2 m x 2 m) + cabbage (50 cm x 50 cm), T3 = Sweet gourd (2m x 2m) + cauliflower (50 cm x 50 cm), T4 = Sweet gourd (2 m x 2 m) + radish (20 cm x 25 cm), T5 = Sweet gourd (2 m x 2 m) + lettuce (50 cm x 50 cm), T6 = Sweet gourd (2 m x 2 m) + tomato (50 cm x 50 cm) were tested at Joydebpur and Rajbari. The highest mean sweet gourd yield (31.37 t ha-1 at Joydebpur and 34.54 t ha-1 at Rajbari) was recorded in sole sweet gourd over the years. The highest mean vegetable yield (42.87 t ha-1 at Joydebpur and 61.40 t ha-1 at Rajbari) was recorded in sweet gourd + cabbage combination. Maximum mean sweet gourd equivalent (SEY) yield (72.55 t ha-1), highest gross return (Tk. 362775 ha-1 and BCR (2.98) were recorded in sweet gourd + cabbage combination over the years at Joydebpur. The maximum mean SEY (79.38 t ha-1), highest gross return (Tk. 396905 ha-1) and BCR (3.25) were recorded in sweet gourd + cauliflower combination at Rajbari. Two year results revealed that sweet gourd + cabbage and cauliflower might be suitable intercrop combination for getting maximum yield and economic return Bangladesh Agron. J. 2018, 21(2): 7-11